Learning object-oriented programming from the students' perspective - Stamouli, Ioanna (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Computer programming and programming languages are core modules in most undergraduate Computer Science and Engineering degree courses. However, learning to program is a complex activity as it involves the understanding and use of abstract concepts, as well as the development of problem-solving and general programming skills. This thesis investigates how students experience learning object-oriented programming by following a group of undergraduate students in Computer Science on an introductory object-oriented programming course.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.